Role of Cysteine Residues in the Structure, Stability, and Alkane Producing Activity of Cyanobacterial Aldehyde Deformylating Oxygenase - Hayashi, Yuuki (PLoS One, 2015)
Aldehyde deformylating oxygenase (AD) is a key enzyme for alkane biosynthesis in cyanobacteria, and it can be used as a catalyst for alkane production in vitro and in vivo. However, three free Cys residues in AD may impair its catalytic activity by undesired disulfide bond formation and oxidation. To develop Cys-deficient mutants of AD, we examined the roles of the Cys residues in the structure, stability, and alkane producing activity of AD from Nostoc punctiforme PCC 73102 by systematic Cys-to-Ala/Ser mutagenesis. The C71A/S mutations reduced the hydrocarbon producing activity of AD and facilitated the formation of a dimer, indicating that the conserved Cys71, which is located in close proximity to the substrate-binding site, plays crucial roles in maintaining the activity, structure, and stability of AD. On the other hand, mutations at Cys107 and Cys117 did not affect the hydrocarbon producing activity of AD. Therefore, we propose that the C107A/C117A double mutant is preferable to wild type AD for alkane production and that the double mutant may be used as a pseudo-wild type protein for further improvement of the alkane producing activity of AD.